Assessment Instruments of STEM Project-Based Learning on Statistical Materials - Rosita Dwi Ferdiani (Universitas Pendidikan Ganesha, 2022)
Most students do not have the skills to use information, so the information is less applicable in everyday life, and can even hurt students. This is a challenge for teachers in this era. One of the learning models that can be used to face challenges in the era of the industrial revolution 4.0 is Project-Based Learning. Therefore the purpose of this study was to analyse the feasibility, practicality, and effectiveness of the STEM project-based learning assessment instrument. The research development model used in this research is ADDIE model. The subjects of this research are two class of junior high school namely class VIII A and class VIII B which will be doing a broad field test. The data collected consists of two kinds, Qualitative and Quantitative. The data collection instrument to be carried out is divided into three category including, 1) product feasibility assessment instrument, 2) product practicality instrument 3) product effectiveness instrument. The result concluded that the STEM Project Based Learning-based learning assessment instrument developed by the researcher was declared